THE ROLE OF SPIRITUAL AND EDUCATIONAL EVENTS IN THE LIFE OF STUDENTS (American Journal of Research in Humanities and Social Sciences, 2025)
This article explores the vital role that spiritual and educational events play in the holistic development of students. These events foster moral and ethical values, promote emotional and psychological well-being, and enhance cultural awareness and identity formation. By providing opportunities for mindfulness, reflection, and community engagement, spiritual activities contribute to personal growth, stress management, and social responsibility. Additionally, such events encourage leadership development and civic engagement, while indirectly supporting academic success by improving focus, emotional resilience, and a positive learning mindset. The article highlights how these experiences are essential for nurturing well-rounded, ethically grounded, and socially responsible individuals.